The role of bio-based cutting fluids for sustainable manufacturing and machining processes: A holistic review - Arun Kumar Katam; Ramesh Chandra Mohanty; Aditya Kolakoti (Mechanical Engineering for Society and Industry, 2023)
Metal cutting fluids (MCFs) play a significant role in cooling and lubricating the cutting zones during various machining operations. The commercially available MCFs like mineral and petroleum oils cater to approximately 75% of the market needs. However, these MCFs harm the worker's health and environment. Therefore, sustainable and eco-friendly MCFs are gaining widespread acceptance in industries. This study critically analyses the recent improvements in metal cutting fluids in drilling, milling, and turning operations with the prospect of accomplishing green and sustainable manufacturing. Furthermore, this study highlights the role of bio-based cutting fluids in the manufacturing industry and the effect of non-bio-based coolants on the environment, and human health hazards are highlighted. In addition, this study analyses minimum quantity lubrication (MQL) techniques applied in various metal-removing operations. Finally, this review article recommends that bio-based cutting fluids combined with MQL techniques can achieve the sustainability goals of the manufacturing industry.